Virus-Like Particles Derived From a Virulent Strain of Pest des Petits Ruminants Virus Elicit a More Vigorous Immune Response in Mice and Small Ruminants Than Those From a Vaccine Strain - Yan, Feihu; Li, Entao; Li, Ling; Schiffman, Zachary; Huang, Pei; Zhang, Shengnan; Li, Guohua; Jin, Hongli; Wang, Hualei; Zhang, Xinghai; Gao, Yuwei; Feng, Na; et al. (Frontiers in Microbiology, 2020)
Peste des petits ruminants (PPR) is an acute or subacute and highly contagious disease of small ruminants, caused by peste des petits ruminants virus (PPRV). Until now, several studies have designed PPRV virus like particles (VLPs) as a vaccine candidate, however no research has compared the immunogenicity of VLPs derived from different PPRV strains in targeted animals. In this study, PPRV VLPs were generated using a baculovirus system through the co-expression of the PPRV matrix (M), hemagglutinin (H) and fusion (F) proteins from both the lineage IV virulent strain China/Tibet/Geg/07-30 and lineage II vaccine strain Nigeria 75/1 in the high expression level cell line BTI-TN5B1-4 cell (High FiveTM). These VLPs were then used to immunize mice, goats and sheep followed by two boosts after primary immunization. Both VLPs were found to induce a potent humoral immune response as demonstrated by the high ratio of IgG1 to IgG2a. In all animals, both VLPs induced high titers of virus neutralizing antibodies (VNAs) as well as H- and F-specific antibodies with the Tibet/30 VLPs yielding higher antibody titers by comparison to the Nigeria 75/1 VLPs. Studies in mice also demonstrated that the Tibet/30 VLPs induced a more robust IL-4 and IFN-γ response than the Nigeria 75/1 VLPs. Goats and sheep immunized with both VLPs exhibited a robust humoral and cell-mediated immune response. Furthermore, our results demonstrated that the VLPs derived from the virulent lineage IV Tibet/30 strain were more immunogenic, inducing a more potent and robust humoral and cell-mediated immune response in vaccinated animals by comparison to the lineage II Nigeria 75/1 vaccine strain VLPs. In addition, VNA titers were significantly higher among animals vaccinated with the Tibet/30 VLPs by comparison to the Nigeria 75/1 VLPs. Taken together, these findings suggest that VLPs derived from the virulent lineage IV Tibet/30 strain are more immunogenic by comparison to those derived from the lineage II Nigeria 75/1 vaccine strain and thus represent a promising vaccine candidate for the control and eradication of PPR.